Assessing the recovery aftermaths of selected disasters in the Gulf of Mexico - Doss, Daniel Adrian (Logistics and sustainable transport, 2018)
This research examined quantitatively in-port grain loading levels during the periods preceding and succeeding selected human-made and natural disasters among U.S. Gulf Coast ports. The array of selected disasters consisted of the 2010 British Petroleum oil spill, the 2011 Mississippi River flood, Hurricane Katrina, Hurricane Gustav, and Hurricane Isaac. The outcomes of the analyses showed that the examined in-port Gulf Coast grain loading activities have not fully recovered and achieved the level of normalcy that existed before the examined cataclysms.
Keywords: hurikani; hurricane Gustav; hurricane Isaac; hurricane Katrina; Mississippi river; reka Misisipi